Impact of the New Generation Reconstituted Surfactant CHF5633 on Human CD4+ Lymphocytes. - Markus Fehrholz; Kirsten Glaser; Silvia Seidenspinner; Barbara Ottensmeier; Tore Curstedt; Christian P Speer; Steffen Kunzmann (PLoS ONE, 2016)
BACKGROUND:Natural surfactant preparations, commonly isolated from porcine or bovine lungs, are used to treat respiratory distress syndrome in preterm infants. Besides biophysical effectiveness, several studies have documented additional immunomodulatory properties. Within the near future, synthetic surfactant preparations may be a promising alternative. CHF5633 is a new generation reconstituted synthetic surfactant preparation with defined composition, containing dipalmitoyl-phosphatidylcholine, palmitoyl-oleoyl-phosphatidylglycerol and synthetic analogs of surfactant protein (SP-) B and SP-C. While its biophysical effectiveness has been demonstrated in vitro and in vivo, possible immunomodulatory abilities are currently unknown. AIM:The aim of the current study was to define a potential impact of CHF5633 and its single components on pro- and anti-inflammatory cytokine responses in human CD4+ lymphocytes. METHODS:Purified human CD4+ T cells were activated using anti CD3/CD28 antibodies and exposed to CHF5633, its components, or to the well-known animal-derived surfactant Poractant alfa (Curosurf®). Proliferative response and cell viability were assessed using flow cytometry and a methylthiazolyldiphenyltetrazolium bromide colorimetric assay. The mRNA expression of IFNγ, IL-2, IL-17A, IL-22, IL-4, and IL-10 was measured by quantitative PCR, while intracellular protein expression was assessed by means of flow cytometry. RESULTS:Neither CHF5633 nor any of its phospholipid components with or without SP-B or SP-C analogs had any influence on proliferative ability and viability of CD4+ lymphocytes under the given conditions. IFNγ, IL-2, IL-17A, IL-22, IL-4, and IL-10 mRNA as well as IFNγ, IL-2, IL-4 and IL-10 protein levels were unaffected in both non-activated and activated CD4+ lymphocytes after exposure to CHF5633 or its constituents compared to non-exposed controls. However, in comparison to Curosurf®, expression levels of anti-inflammatory IL-4 and IL-10 mRNA were significantly increased in CHF5633 exposed CD4+ lymphocytes. CONCLUSION:For the first time, the immunomodulatory capacity of CHF5633 on CD4+ lymphocytes was evaluated. CHF5633 did not show any cytotoxicity on CD4+ cells. Moreover, our in vitro data indicate that CHF5633 does not exert unintended pro-inflammatory effects on non-activated and activated CD4+ T cells. As far as anti-inflammatory cytokines are concerned, it might lack an overall reductive ability in comparison to animal-derived surfactants, potentially leaving pro- and anti-inflammatory cytokine response in balance.